Social Media Responsibility towards COVID 19 News: The Case of Qatar - Galal, Ashraf; Auter, Philip J. (Dirasat: Human and Social Sciences, 2023)
Objectives: This study explored to what extent people in one nation in the Middle East, Qatar, used social media to obtain information regarding COVID-19. It also looked at how social media organizations review and attempt to verify posted information and what they do when and if they discover fake news Methods: The researchers surveyed 400 Qatari citizens to determine their perceptions of the credibility of government and private social media sites and how that differed from their perception of the credibility of traditional mass media news outlets.The research also addressed the interrelationship between browsing social media for information and disinformation about COVID-19 and a person’s feelings of threat, anxiety, and fear. Results: The study found that social media users may have difficulty telling the difference between information and disinformation. This can increasetheir fear, anxiety, and stress. This relationship appears to be clear, and cuts across all demographic lines. What is unclear is whether fear drives people to increase their social media searching for COVID-19 information, or if increased consumption increases fear? It’s quite possible that it is a circular relationship. Conclusions: The study recommended that interventions from multiple stakeholders are essential in order to rationale social media performance and harness it’s power to disseminate reliable information.